Correction: Dietary Diversity, Diet Cost, and Incidence of Type 2 Diabetes in the United Kingdom: A Prospective Cohort Study. - PLOS Medicine Staff (PLoS Medicine)
Corrected publisher error in data availability statement. [This corrects the article DOI: 10.1371/journal.pmed.1002085.].